DESKRIPSI KEMAMPUAN PESERTA DIDIK TINGKAT SMA MENYELESAIKAN SOAL HOTS MATERI HUKUM-HUKUM DASAR KIMIA - Annisa Wulandari; Hairida Hairida; Masriani Masriani (Universitas Tanjungpura, 2020)
AbstractThis research is aimed to describe the ability of high school students in solving HOTS questionstchemistrybasic law. This research use descriptive qualitative method, with the subjects of class XI students of SMA Negeri 5 Pontianak, SMANegeri 6 Pontianak, SMA Negeri 9 Pontianak, SMA Negeri 2 Kubu Raya, totaling 127 students. The instrument used in the form of HOTS questions with the cognitive level of analyzing (C4) and evaluating (C5). The validation results show that the instrument used has a very good level of validity with an average percentage of small scale of 95.41% with a very high category and an average percentage of large scale of 93.75% with a very high category. The reults showed that the percentage of students ability insolving HOTS questions is 19,9%.Keyword: Basic Laws of Chemistry, Description, HOTS